Digital Citizenship in the Dynamics of Post-Digital Education - Feriyansyah; Siti Murtiningsih; Hastanti Widy Nugroho (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2026)
This study examines the dynamics of digital citizenship in post-digital education through the lens of Henry Giroux's critical pedagogy philosophy. This research is motivated by digital transformation, with the primary concern being the issue of technological determinism in education, which overlooks the need for emancipatory critical awareness. This inquiry philosophy research is based on literature related to post-digital education as a material object and critical pedagogy as a formal object. Methodologically, the study elaborates interpretation, induction and deduction, internal coherence, holism and historical continuity, comparison, heuristics, language inclusiveness, and in-depth reflection on formal and material objects in philosophical research. The study found that Giroux's critical pedagogy positions education as an ethical and political arena against dehumanization in the digital era. The rationality of post-digital education requires metaphysical and epistemological reflection to affirm the existence and implementation of humanistic values in post-digital educational practices. Conceptually, encouraging digital citizenship education to develop beyond technical competence into an emancipatory project of political awareness. So that students critically question their existence in digital power structures. Critical digital citizenship education fosters adaptive, ethical, and sensitive responses to social issues in uncertain future scenarios.